The Effect of Foot Soaking Therapy with Ginger Water on the Level of Pain in Gout Arthritis Patients at the Central City Health Center - Wanda Ayu Nita; Nurdiana Djamaluddin; Erwin Purwanto (Universitas Muhammadiyah Palu, 2026)
Gout arthritis triggers acute pain that interferes with mobility. At the Central City Health Center, there were 459 cases with a tendency for patients to avoid chemical drugs. Warm ginger water foot soaking therapy comes as a nonpharmacological alternative that takes advantage of the thermal and phytochemical effects of ginger. This Quasi-Experimental quantitative research with Non-Equivalent Control Group Design involved 36 respondents who were selected by purposive sampling. Respondents were divided into intervention groups (warm ginger water) and control (warm water). The pain scale was measured using the Numeric Rating Scale (NRS) and analyzed using the Wilcoxon and Mann-Whitney tests. The majority of respondents were men (56%) with an age range of 41-50 years (44%). Both groups showed a significant reduction in pain after the intervention (p=0.000). Although the decline in the ginger group was slightly higher, the intergroup test showed no significant difference in effectiveness (p=0.318). Soaking your feet in warm ginger water and regular warm water are equally effective in relieving gout arthritis pain. This therapy is recommended as a safe and economical independent pain management for the community.